Diana's White House garden - Carbone, Elisa (Viking, Penguin Young Readers Group, 2016)
"It's 1943, and the White House is busy with the war effort. Diana Hopkins only wants to help, but doesn't know what a ten-year-old can do - until the Roosevelts come up with the idea of Victory Gardens, and Diana suddenly has the important job of Victory Gardener for the White House"--